SEASONAL FLUCTUATIONS OF INDICES OF INFESTATION OF ECTOPARASITES OF THE FAMILY MUGILIDAE WITH EMPHASIS ON MUGIL CUREMA IN A TROPICAL ESTUARY (BRAZIL) - CAMPELO, Renata Polyana de Santana; FONSECA, Francinete Torres Barreiro da; DÍAZ, Xiomara Franchesca Garcia; SCWHAMBORN, Ralf (Revista Nordestina de Zoologia, 2014)
The seasonal changes of the aquatic environment affecting qualitative and quantitative parasitic indices of infection for ectoparasites of tropical Mugilidae fish are still little known. This study aimed at verifying the seasonality effect in the rates of infestations of ectoparasites of Mugilidae fish in an urban estuary in northeastern Brazil. 90 specimens of Mugilidae were sampled for each collection period (dry and wet) in the estuary of Pina Basin / Pernambuco, Brazil. The identification to species level and inspection for parasitological examination was performed in laboratory. The parasitological analysis resulted in the identification of 3851 individuals collected in the dry season, Monogenea was the most abundant taxon with 1739 individuals (45.15%) of the total quantified parasites, parasitizing 28 (31%) out of the hosts analyzed. 2871 specimens were recorded in the rainy season, the class Myxosporea stood out with 2453 individuals (84.3%) of the total collected ectoparasites parasitizing 31 (34%) of the hosts analyzed. The copepod Ergasilus lizae had the highest prevalence in the dry season (43.50%). The protozoan Myxobolus sp. had the highest prevalence (35.20%), intensity (79.12) and mean abundance (27.8) in the rainy season. The seasonally influenced the indices of infestation of Ligophorus sp. and Ergasilus lizae. Myxobolus sp. had its prevalence influenced by seasonality. The seasonal effect is evident in the high indices registered for intensity and abundance of Ligophorus sp. in the dry period and Myxobolus sp. in the rainy season which would mean an indication of environmental impacts in the study area.